Artefact-to-Legal Element Mapping in iOS-Based Web Gambling Cases: A Cross-Source Correlation Framework under KUHP and ITE Law - Sudirman Sudirman; Yudi Prayudi (Universitas Ahmad Dahlan, 2026)
The widespread use of web-based online gambling through mobile browsers and instant messaging applications has made digital traces increasingly difficult to interpret as legally admissible evidence. Previous forensic research primarily concentrated on artefact recovery from dedicated gambling applications, leaving limited attention to systematic approaches for associating web-based traces with legal elements. This study examined the identification, classification, and legal mapping of web-based gambling artefacts using the proposed Artefact-to-Legal Element Mapping Framework (ALMF). A real-case evidence set acquired from an Apple iPhone XR was analysed with Magnet AXIOM Process v9.4.0.44917, generating Quick Image and Decrypted evidence for extraction and correlation. The analysis identified four major artefact categories, including web browsing traces, credential and persistence artefacts, WhatsApp communication records, and visual media files. Browser artefacts reflected intentional discovery and access to gambling websites, whereas credential artefacts indicated recurring or sustained access. WhatsApp conversations provided the strongest evidence of promotional activities through shared links, invitations, and dissemination patterns. Visual artefacts further strengthened the gambling context by revealing website interfaces and financial indicators. Cross-source correlation differentiated player activities from promoter or distributor behaviour. The mapped evidence supported KUHP Article 303 and UU ITE Article 27(2). The findings demonstrated that contextual interpretation across multiple artefact sources produced stronger evidential value than analysing individual artefacts separately.